Características principales, logros y dificultades de la gestión de la investigación en el Nivel Superior y su correlato en las publicaciones - María Isabel Pozzo (Universidad Nacional, Costa Rica, 2008)
In this article, the main characteristics, achievements and difficulties in research and publishing management in higher education are presented, taking into account the experience of the author in the institutions to which she belongs (Teacher Trainning College and Graduate and Post graduate university levels) in Argentina. The presentation seeks to foster institutional exchange of experiences from sharing strategies that may help develop research activities as a key factor in teacher trainning.